2009
DOI: 10.1177/0306624x08328755
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Actuarial Risk Assessment

Abstract: This study examines the predictive validity of the most commonly used risk assessment instruments for sexual offenders: Static-99, Rapid Risk Assessment for Sexual Offense Recidivism, Sex Offender Risk Appraisal Guide, Sexual Violence Risk-20, and Psychopathy Checklist-Revised in a prospective research design. Although risk assessment is part of a regime leading to various efforts to reduce risk by treatment and aftercare, all instruments show good predictive validity. However, depending on the instrument, rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
0
5

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 40 publications
6
53
0
5
Order By: Relevance
“…The relatively high mean age of the pedophilic participants may be reflective of the average age of child sexual abusers in correctional settings, however. A large descriptive study by Eher and colleagues [43,44], for instance, reported a mean age of 43.4 years (range: 16-71 years) for a sample of 430 sexual abusers of children from Austria.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively high mean age of the pedophilic participants may be reflective of the average age of child sexual abusers in correctional settings, however. A large descriptive study by Eher and colleagues [43,44], for instance, reported a mean age of 43.4 years (range: 16-71 years) for a sample of 430 sexual abusers of children from Austria.…”
Section: Discussionmentioning
confidence: 99%
“…Agreement for effect size coding was 96.7%, with two disagreements resulting from a coder failing to note that two small d values from the same study were negative and a third arising from miscalculation of an odds ratio from a 2 X 2 table. The coding process identified four studies for which it was unclear whether the researchers had used field or research scores, or file-only as opposed to file-plus-interview scoring (e.g., Beggs & Grace, 2008;Dufresne, 2006;Gonsalves et al, 2009;Rettenberger, Matthes, Boer, & Eher, 2010). We contacted and received responses from the corresponding authors from each of these studies that allowed us to code them appropriately (i.e., each used file plus interview, all used field scores; although Gonsalves et al, 2009, used both field and research scores).…”
Section: Coding Proceduresmentioning
confidence: 99%
“…Inter-rater reliability By calculating intraclass correlation coefficients (ICCs), the inter-rater reliability of the Static-2002 was excellent (ICC = .90, p < .001). In a previous study, the inter-rater reliability of the Static-99 was also found to be excellent (ICC = .98, p < .001; Rettenberger et al, 2010).…”
Section: Risk Scale Scoresmentioning
confidence: 73%
“…Therefore, the aim of this study was to investigate the predictive accuracy of the Static-2002 using a German adaptation of the Static-2002 in the German-speaking offender population. Previous studies showed that internationally well-established structured risk assessment instruments yielded also by using German-speaking samples high reliability and validity indices (Eher et al, 2012;Rettenberger et al, 2010;Stadtland et al, 2005). Therefore, we hypothesized that an examination of the psychometric properties of the Static-2002 in a German-speaking sample would yield effect sizes that are comparable to the above-mentioned international studies.…”
mentioning
confidence: 72%
See 1 more Smart Citation